Sensory Quality Evaluation of Moisturising Hand-care Cosmetic Products - Szakiel, Jerzy; Turek, Paweł (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The aim of the article was to evaluate the sensory quality of moisturising cosmetic products for hand skin care. The evaluation was performed on a group of 10 products available for retail sale. The assessment was performed in a sensory analysis laboratory equipped with individual assessment stations by trained and selected assessors, using a five-point test. The results made it possible to calculate an overall quality factor. Based on factor values, products were classified according to appropriate quality classes. Five of the products tested made it into the “good” quality class, while the other half fell to the “sufficient” class. A lack of statistically significant correlation between the level of sensory quality of the products and their price was also confirmed.